BARRIERS, FACILITATORS AND SOCIO-DEMOGRAPHIC CHARACTERISTICS ASSOCIATED WITH CONDOM USAGE AMONGST MALE HIV INTEGRATED COUNSELLING AND TESTING CENTRE ATTENDEES AT THE GOVERNMENT HOSPITAL OF THORACIC MEDICINE, AN HIV TERTIARY CARE CENTRE IN CHENNAI - Mahajan, D; Ottilingam, K R; Gurusamy, M; Chokkalingam, C (Indian Journal of Community Health, 2013)
Background: HIV is transmitted largely through sexual route which can be prevented by using condoms. The objectives of this study were to describe condom usage with various barriers, facilitators and to determine association between different socioeconomic characteristics among male Integrated Counselling and Testing Centre (ICTC) attendees. Methods: This is a hospital based cross sectional study (n=300). Clients (18-45years) attending ICTC for first time, between June-October ‘2010, were interviewed with structured questionnaire after obtaining informed consent. Description of demographic characteristics of respondents; univariate, multivariate logistic regression analyses were performed for estimation of association. Results: Among respondents, awareness of HIV and condom were 80% and 85.3% respectively; Knowledge of prevention from STI/HIV (97.7%) was most common facilitator while forgetfulness after drinking alcohol (64.1%) was most common barrier to use condom; Respondents who had education up to secondary or above level were more associated with condom usage (AOR 2.9,95%CI1.34-6.24, after adjusting for income) compared to non educated respondents; considering less than Indian rupee (INR) 3000 per month as reference category, there were association of condom usage among relatively higher income groups between INR.3000 to 5000 per month (AOR 2.6, 95%CI 1.38-5.0,adjusting education) and income above INR5000 per month (AOR 2.85,95%CI1.37-5.9, adjusting education). Conclusions: Condom usage was independently associated with education and income level of respondents. Forgetfulness after drinking alcohol was main barrier; knowledge of prevention from HIV was main facilitator of condom usage. Dissemination of knowledge regarding facilitator of condom usage and implementation of Rapid Needs Assessment Tool for Condom Programming can encourage condom use.